Konstruksi Peran Perempuan dalam Menyikapi Pernikahan pada Podcast Suara Berkelas Episode “Bedah Mindset Perempuan Berkelas #67 - Ilza Catur Nikmatus; Nabila Saviratus Zahirah (Indo Publishing, 2025)
This study aims to examine how women’s roles in navigating marriage are socially constructed through the dialogue presented in Episode 67 of the Suara Berkelas podcast. The research is motivated by the persistence of social expectations that position women as the primary bearers of domestic responsibilities, emotional labor, and pressure to marry at a certain age. The study seeks to identify how the speaker negotiates, challenges, and reconstructs these expectations through personal experiences and reflections on marital readiness, division of roles, and partner independence. Using a descriptive qualitative approach with content analysis, the study applies Berger and Luckmann’s social construction theory along with Simone de Beauvoir’s concept of gender construction. The findings show that the speaker actively articulates a new narrative that positions women as empowered, rational agents with full authority over major life decisions, including marriage. Ideas such as shared household responsibilities, emotional maturity, support for women’s careers, and marrying at a more mature age emerge as alternative constructions that contest patriarchal norms. The study concludes that the podcast serves as a medium for shaping alternative discourses that strengthen women’s position within marriage. This research recommends increased production of media content that centers women’s experiences and supports public education policies promoting gender equality within families and marital decision-making.